ChemInform Abstract: Panthogenins A and B, Two Novel Norergostanol Steroids from Dioscorea panthaica. Issue 10 (March 2015) - Shan, Xiao‐Qing; Peng, Shu‐Lin; Shi, Hai‐Li; Wang, Xiao‐Ling; Ding, Li‐Sheng; Liao, Xun
Abstract Panthogenins A (I) and B (II), two novel norergostanol steroids containing a unusual seven‐membered ring, are isolated.